New Perspective On The ‘Net Errors And Omissions’ In Balance Of Payment Accounts: An Empirical Study In Australia - tang , tuck cheong (Asian Academy of Management (AAM), 2017)
This study explores the macroeconomic determinants of the ‘net errors and omissions’ behaviour in balance of payment accounts. Two empirical equations are being estimated as suggested by the balance of payments constraint, and income-expenditure approach, respectively. This study fnds that GDP, interest rate, and exchange rate are the important factors explaining the Australian ‘net errors and omissions’. Causality tests have recognized the possible transmission channels. This study can be considered a new perspective in this topic and reference for further research.